Parc tecnològic
Proyecto para la construcción de un complejo urbano dedicado a la tecnología.
Keywords: FOSTER ASSOCIATES; FOSTER, NORMAN; ALEMANIA; NORTH RHINE-WESTPHALIA; DÜSSELDORF; DUISBURG; CENTROS TECNOLOGICOS; PAQRUES TECNOLÓGICOS; PROYECTOS